Lésbicas, família de origem e família escolhida: um estudo de caso - Cancissu, Cynthia Regina Pemberton (2007)
This study discusses the lesbian relational net, the presence of a family of choice and how these relationships are built. To better understand this phenomenon a qualitative research was made with a case study and a semi-structured interview. The person whose case was used was a homosexual woman, out of the closet, older than 30 and who had lived more than one important homosexual romantic relationship. The study also discusses matters as the construction of the homosexual identity, the process of coming out, especially for the family of origin, the relationship between the homosexual and his family of origin and the construction of new relationships, specially the ones within the lesbian community. This study demonstrated the difficulties the individual lives when facing its own homosexuality and the distress she has when coming out for her family of origin. The family s reactions leads the participant in a search for a supporting net, found in the lesbian community. Since than, she starts the construction of a new set of relationships, friendships, romantic and ex-lovers relations that together will form her family of choice. At the same time, the relationship with her family of origin passes through several changes until full acceptance of her homosexuality. Finally, these relational net and the family of origin are blended to form her family of choice that reflects the complexity of these relationships